Inorganic controlled release technology : materials and concepts for advanced drug formulation - Zhang, Xiang; Cresswell, Mark (Elsevier : BH, 2016)
Inorganic Controlled Release Technology: Materials and Concepts for Advanced Drug Formulation provides a practical guide to the use and applications of inorganic controlled release technology (iCRT) for drug delivery and other healthcare applications, focusing on newly developed inorganic materials such as bioresorbable glasses and bioceramics. The use of these materials is introduced for a wide range of applications that cover inorganic drug delivery systems for new drug development and the reformulation of existing drugs. The book describes basic concepts, principles, and industrial practic.